Abstract 203: Predicting Outcomes After Mechanical Thrombectomy: Early vs Delayed Neurological Improvement in the SELECT Database - K. Rose Duncan; Deep Pujara; Amrou Sarraj (Stroke: Vascular and Interventional Neurology)
Introduction Understanding of patient benefit and improvement following mechanical thrombectomy in ischemic stroke has made tremendous strides in recent years, however clinicians still struggle to accurately predict patient outcomes and long‐term neurological functioning following large vessel occlusion and endovascular therapy. These limitations are further complicated by a highly variable time course of improvement following intervention that spans from minutes to months. Prior literature has shown that successful reperfusion is associated with better outcomes even in the absence of early improvement. Delayed neurological improvement may be the result of microvasculature effects and inflammatory changes, and is likely multifactorial. Improved understanding of predictors of early versus delayed neurological improvement in this population may help inform goals of care, aid in clinical decision making, and manage patient and family expectations. Methods Patient data from the SELECT database was retrospectively analyzed. The SELECT study was a prospective, non‐randomized, multicenter cohort study that enrolled patients with acute ischemic stroke due to anterior circulation large vessel occlusion at nine US centers between 1/2016 and 2/2018, with patients falling into either the mechanical thrombectomy or medical management arm. Only patients in the mechanical thrombectomy arm (n=149) were included in this analysis. Possible predictors of early vs late neurological improvement were segregated into pre‐procedure (age, NIHSS at baseline, IV thrombolytic therapy, transfer status, occlusion location, ischemic core, ischemic penumbra, hypoperfusion intensity ratio, successful reperfusion, type of anesthesia, time from last known well to puncture, time from puncture to reperfusion) and post‐procedure (NIHSS at 24‐hour follow‐up, ASPECTS on follow‐up imaging, ASPECTS point loss from baseline, infarct volume on follow‐up imaging, infarct growth from baseline ischemic core, neurological worsening, midline shift, hemorrhagic transformation and type). Backwards stepwise regression was used to identify significant predictors of early and delayed improvement. Results Pre‐procedure predictors of early neurological improvement (defined as mRS 0‐2 at discharge) were age (p=0.001), NIHSS score (p=0.002), ischemic core volume (p=0.001), transfer status (p=0.019), and successful reperfusion (defined as mTICI 2b or better, p=0.001). Post‐procedure predictor of early neurological improvement was NIHSS score at 24 hours (p<0.001). Pre‐procedure predictor of delayed neurological improvement (defined as mRS 0‐2 at 90 days among those who did not achieve early neurological improvement) was ischemic core volume (p=0.003). Post‐procedure predictors of delayed neurological improvement were final infarct volume (p=0.012), change in ASPECTS on follow‐up imaging (p=0.001), and growth in infarct size (p=0.030). Pre‐procedure predictors of early excellent outcome (defined as mRS 0‐1 at discharge) were age (p=0.001), NIHSS score (p<0.001), successful reperfusion (p=0.001), ischemic core volume (p=0.004), and infarct growth rate (p=0.034). Pre‐procedure predictor of delayed excellent outcome (defined as mRS 0‐1 at 90 days among those who did not achieve early excellent outcome) was NIHSS score (p=0.002). Additionally, midline shift of 5mm or more at 24 hours was associated with poor outcome at 90 days. Conclusion Several demographic, imaging, and clinical factors were found to correlate with either early or delayed neurological improvement. Further investigation may help delineate how these predictors can be utilized to inform clinical decisions and discussions regarding stroke patients receiving mechanical thrombectomy.